2002
DOI: 10.1111/j.1749-6632.2002.tb04630.x
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP Induces Phosphatidylserine Externalization Earlier than Nuclear Apoptotic Events in Thymocytes

Abstract: The present study shows for the first time that ATP(ec) induces a very early PS exposure in thymocytes and that this process can be induced in the absence of Ca(2+) influx and caspase activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…In the present study, we found that ATPe triggers PS externalization in plasma membrane of thymocytes from BALB/c mice within 15 min. BzATP also triggers a rapid PS flip in HEK 293 cells expressing the P2X7R, in THP-1 monocytes (46) and in mouse thymocytes (47). However, because translocation of PS induced by P2X7R can be dissociated from apoptosis (46), we analyzed the effect of ATPe on DNA fragmentation, a late event in the apoptotic process.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that ATPe triggers PS externalization in plasma membrane of thymocytes from BALB/c mice within 15 min. BzATP also triggers a rapid PS flip in HEK 293 cells expressing the P2X7R, in THP-1 monocytes (46) and in mouse thymocytes (47). However, because translocation of PS induced by P2X7R can be dissociated from apoptosis (46), we analyzed the effect of ATPe on DNA fragmentation, a late event in the apoptotic process.…”
Section: Discussionmentioning
confidence: 99%
“…At physiological external concentrations, Na ϩ was more potent than Ca 2ϩ to induce PS exposure. Portions of this work have appeared in a preliminary report (31).…”
mentioning
confidence: 99%
“…6 A third category, P2Z, which caused ATP-dependent cell lysis by the formation of membrane pores permeable to large molecules, was found to have P2X function as well and has been reclassified as P2X7. 7 Since Burnstock's discovery of ATP receptors in the nervous system, the subtypes of the P2X and P2Y receptor families have been found in diverse cell types throughout the body, including the cardiovascular, [8][9][10][11][12] respiratory, [13][14][15][16] gastrointestinal, 17-20 urogenital, 21-27 musculoskeletal, 28-32 and endocrine 33-37 systems, and play particularly prominent roles in the development 38 and function 39 of the immune system. Extracellular ATP has been implicated in some stage of progression of pathologic processes ranging from atherosclerosis 40,41 to stroke 42 to arthritis 43 to gastric ulcers.…”
Section: Sommairementioning
confidence: 99%